(untitled) (World Bulletin of Management and Law, 2022)
With the growth of the sharing economy, co-working is becoming a phenomenon of global importance. As the number of co-working spaces in the world’s leading metropolitan cities has increased, in recent years more and more knowledge workers who are most active in the creative industry sector have begun to take advantage of the shared urban office environment known as co-working spaces. As a result of these assumed benefits for knowledge creation, co-working spaces have been conceptualized as microgroups in analogy to what groups can be understood as. The results of the thematic data analysis show that the main factors are considered effective in their ability to drive the dynamics of knowledge creation in co-working spaces. “Geographical concentration of interconnected companies, specialty suppliers, service providers, companies from related industries, and related institutions.” these factors are actually considered to be effective by key actors related to co-working spaces. Thematic data analysis shows four main factors that are considered to be effective in their ability to cultivate in-depth knowledge in co-working spaces namely choosing, combining, Interactive design, and developing in co-working spaces